The 2022 World Health Organization Classification of Tumors of the Urinary System and Male Genital Organs-Part B: Prostate and Urinary Tract Tumors. - Netto, George J.; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Raspollini, Maria R.; Rubin, Mark A.; Srigley, John R.; Hoon Tan, Puay; Tickoo, Satish K.; et al. (European Urology, 2022)
The 2022 World Health Organization (WHO) classification of the urinary and male genital tumors was recently published by the International Agency for Research on Cancer. This fifth edition of the WHO "Blue Book" offers a comprehensive update on the terminology, epidemiology, pathogenesis, histopathology, diagnostic molecular pathology, and prognostic and predictive progress in genitourinary tumors. In this review, the editors of the fifth series volume on urologic and male genital neoplasms present a summary of the salient changes introduced to the classification of tumors of the prostate and the urinary tract.
EVALuna2:542933